More than a game: strengthening subject-literacy through role-play in a content and language integrated classroom - Segura Hudson, Marta (Frontiers in Education, 2025)
This study presents findings based on the observation of a United Nations role-play task in a plurilingual high school (age of students 16–19) where CLIL pedagogical approaches are practiced. The integration and scaffolding of course content in the subjects of International Relations, History, Social Studies and English is explored via examples of student language use in learners of English. Formal and informal examples of prepared as well as spontaneously produced speech have been collected in a specialized learner corpus and are being analyzed in reference to subject-literacy aims. This “game” provided a rich arena for students to practice skills such as public speaking and debate, negotiation, and the writing of texts such as resolutions, presentations of policy and reflections. Through this integrated approach to learning students further consolidated subject matter knowledge gained during study of the history of conflict in the Middle East, with new understandings of geopolitical interests via the policy precedents set by the nations studied, together with language suitable to express this knowledge. Furthermore, students developed arguments for or against perspectives, which they held regarding the conflict in question. This exercise illustrates integration of language and content learning with the potential for lasting and transformative learning outcomes, beyond assessment. It also provides an authentic example of simultaneous language learning and subject-literacy practices, responding directly to the question of how learning in L2 affects subject knowledge in this academic environment.